1995
DOI: 10.1007/bf02229172
|View full text |Cite
|
Sign up to set email alerts
|

Brain electrical activity (quantitative EEG and bit-mapping neurocognitive CNV components), psychometrics and clinical findings in presenile subjects with initial mild cognitive decline or probable Alzheimer-type dementia

Abstract: Clinical, neuropsychological and neuropsychophysiological data (Q-EEG, ERPs and CNV/RT activity) were obtained from 24 patients who had more or less severe presenile primary cognitive decline without depression, and compared with similar data from 10 age-matched healthy volunteers (mean age, 59.4 years). All of the patients (15 M and 9 F; mean age 59.6 years) were selected according to the DSM III-R, ICD-10 and NINCDS-ADRDA criteria and underwent CT and MRI scanning, in addition to a standard clinical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 135 publications
0
53
0
Order By: Relevance
“…Recent postmortem data from subjects -who had been prospectively followed and clinically characterized up to immediately before their death -indicate that hippocampal choline acetyltransferase levels are reduced in Alzheimer's dementia, but in fact they are upregulated in MCI (Lavenex and Amaral, 2000;DeKosky et al, 2002), presumably because of reactive upregulations of the enzyme activity in the unaffected hippocampal cholinergic axons. Previous EEG studies (Babiloni et al, 2000;Jelic et al, 2000Jelic et al, , 1996Ferreri et al, 2003) have shown a decrease -ranging from 8 to 10.5 Hz (low alpha) -of the alpha frequency power band in MCI subjects, when compared to normal elderly controls (Zappoli et al, 1995;Huang et al, 2000;Jelic et al, 2000;Koenig et al, 2005;Babiloni et al, 2006a). However, a recent study has shown an increase -ranging from 10.5 to 13 Hz (high alpha) -of the alpha frequency power band, on the occipital region in MCI subjects, when compared to normal elderly and AD patients (Babiloni et al, 2006a).…”
Section: Introductionmentioning
confidence: 95%
“…Recent postmortem data from subjects -who had been prospectively followed and clinically characterized up to immediately before their death -indicate that hippocampal choline acetyltransferase levels are reduced in Alzheimer's dementia, but in fact they are upregulated in MCI (Lavenex and Amaral, 2000;DeKosky et al, 2002), presumably because of reactive upregulations of the enzyme activity in the unaffected hippocampal cholinergic axons. Previous EEG studies (Babiloni et al, 2000;Jelic et al, 2000Jelic et al, , 1996Ferreri et al, 2003) have shown a decrease -ranging from 8 to 10.5 Hz (low alpha) -of the alpha frequency power band in MCI subjects, when compared to normal elderly controls (Zappoli et al, 1995;Huang et al, 2000;Jelic et al, 2000;Koenig et al, 2005;Babiloni et al, 2006a). However, a recent study has shown an increase -ranging from 10.5 to 13 Hz (high alpha) -of the alpha frequency power band, on the occipital region in MCI subjects, when compared to normal elderly and AD patients (Babiloni et al, 2006a).…”
Section: Introductionmentioning
confidence: 95%
“…The quantitative analysis of electroencephalographic (EEG) rhythms in resting subjects is a low-cost but still powerful approach to the study of elderly subjects in normal aging, MCI and dementia (Gueguen et al, 1991;Maurer and Dierks, 1992;Leuchter et al, 1993;Schreiter-Gasser et al, 1993;Zappoli et al, 1995;Jelic et al, 1996Jelic et al, , 2000Huang et al, 2000;Bennys et al, 2001;Koenig et al, 2005;Babiloni et al, 2006a,b;Prichep et al, 2006;Rossini et al, 2006). The anchor point for a quantitative analysis of the EEG is the a rhythm, which dominates the EEG power spectrum in resting, awake and healthy subjects (Elul, 1972;Lopes da Silva et al, 1976Steriade and Llinas, 1988;Singer, 1993;Destexhe and Sejnowski, 1996;Klimesch, 1997Klimesch, , 1999Pfurtscheller and Lopes da Silva, 1999;Nunez et al, 2001;Suffczynski et al, 2001;Klimesch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of MCI conversion to AD, two longitudinal studies proposed various quantitative EEG parameters for an a priori distinction between PMCI and stable MCI (SMCI) [13,14] . However, cross-sectional comparisons revealed a substantial overlap in these parameters between MCI patients and elderly controls [10,11,14,17] . Methodological differences including variable clinical definition of MCI cases and substantial interindividual differences within the MCI group could partly explain these discrepancies.…”
mentioning
confidence: 99%
“…In this context, electroencephalography (EEG) is an easily accessible and low-cost modality that might prove to be a particularly powerful tool for the identification of subtle functional changes preceding structural or metabolic deficits in PMCI. Most previous contributions in this field assessed quantitative EEG differences between healthy controls, MCI and AD cases leading to contradictory data [9][10][11][12][13][14][15][16][17] . In terms of MCI conversion to AD, two longitudinal studies proposed various quantitative EEG parameters for an a priori distinction between PMCI and stable MCI (SMCI) [13,14] .…”
mentioning
confidence: 99%